Generative Semantics, Generative Morphosyntax. (12th September 2012) - Williams, Edwin
Abstract : Abstract. "GSGM" builds no syntactic structures; rather, semantics and morphosyntax are both generative and run in parallel, and so have no need of mediating syntactic structure. In this environment, positing different modes of embedding for NPs and clauses, as inWilliams 2003, affords new minimal accounts of movement, scope, agreement, and the bounds on them. Syntax/morphosyntax is instantiated as a single parameterized function ("Combine"). Combine derives both mirroring and nonmirroring structure, as any theory must, but in distinctive "size‐relative" patterns determined by its parameters.